“ANALISIS PENGARUH KUALITAS LAYANAN (RELIABILITY, RESPONSIVENESS, ASSURANCE, EMPATHY, TANGIBLE) TERHADAP KEPUASAN SPBU” - Tony Kurniawan (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2013)
This study was conducted to see the effect of the quality of service in terms of tangibles, reliability, responsiveness, assurance, and empathy given by PT Pertamina (Persero) fuel Terminal of “Rewulu” to gas stations it serves. This study was conducted in January 2013. From the calculated regression equation Y = 0.358 X1 + 0.181 X2 + 0.220 X3 + 0.186 X4 + 0.101 X5. From the results of these equations, it is known that the best quality of service is seen from the tangible dimension, as well as most in need of more attention to quality improvement is due to having the smallest value in terms of empathy. Where overall, the fifth dimension is to give effect to the satisfaction of the gas station. Based Test Coefficient of Determination (R2), adjusted R value is 0.670 and it can be concluded that the 67.0% rate of customer satisfaction can be explained by the variable tangibles, reliability, responsiveness, assurance, and empathy. The remaining 33% are other variables that are not included in the test parameters. Respondents who filled out questionnaires were distributed as many as 133 stations, which when viewed in terms of the products they sell to the public, there are 133 stations that distribute the premium product, 129 gas station that distribute biodiesel, 116 stations that distribute pertamax, and 3 gas stations that distribute pertamax plus. In terms of respondents, the distribution of the former gas station fuel Rewulu Terminal, where most of the gas stations in the district of Sleman by the number of 32 stations. While the least is the Klaten district as much as 3 stations Keywords: tangibles, reliability, responsiveness, assurance, empathy and satisfaction of the gas station.